2017
DOI: 10.4314/ejhs.v27i2.14
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic ectopia cordis in an Ethiopian neonate

Abstract: BACKGROUND: Ectopia Cordis is defined as complete or partial displacement of the heart outside the thoracic cavity. It is a rare congenital defect with failure of fusion of the sternum with extra thoracic location of the heart. The estimated prevalence of this case is 5.5 to 7.9 per million live births. CASE PRESENTATION: We had a case of a 16-hour-old male neonate weighing 2.9kg with externally visible, beating heart over the chest wall. Initial treatment included covering the heart with sterile-saline soaked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…This study also revealed that women who were able to organize childcare for their existing children at home during their absence were more likely to express the intention to use an MWH compared to their counterparts. This finding is in agreement with those of studies conducted in Zambia, a rural health center in Ethiopia, Jimma district, and Eastern Gurage [ 10 , 11 , 13 , 21 ]. This may be due to the commonly held societal belief that women, especially those living in rural areas, carry the burden of the childcare responsibilities.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study also revealed that women who were able to organize childcare for their existing children at home during their absence were more likely to express the intention to use an MWH compared to their counterparts. This finding is in agreement with those of studies conducted in Zambia, a rural health center in Ethiopia, Jimma district, and Eastern Gurage [ 10 , 11 , 13 , 21 ]. This may be due to the commonly held societal belief that women, especially those living in rural areas, carry the burden of the childcare responsibilities.…”
Section: Discussionsupporting
confidence: 93%
“…Finally, this study found that the likelihood of expressing an intention to use an MWH was higher among pregnant women who could afford food while staying at an MWH. This is consistent with the findings of studies conducted in a rural health center of Ethiopia and Jimma district [ 10 , 21 ]. This could be due to an inability find a family member or attendant who can provide them with a continuous supply of food, often requiring travelling significant distances, during their stay at an MWH.…”
Section: Discussionsupporting
confidence: 93%
“…A cluster of 13 papers specified radiation exposure during pregnancy as a concern [ 19 , 33 , 34 , 62 , 70 , 76 , 105 , 107 , 132 , 148 , 188 , 202 , 203 ].…”
Section: Resultsmentioning
confidence: 99%
“…The result is also in similar with other findings of different ethnobotanical studies done in somewhere else in Ethiopia and other countries, which have a lack of missed diagnosis and precision as a shortcoming of the traditional healers’ treatment. 8 , 9 , 49 …”
Section: Discussionmentioning
confidence: 99%